Does auditory attentional bias determine craving for methamphetamine? A pilot study using a word recognition dichotic listening task. Issue 11 (November 2022) - Kazemitabar, Maryam; Kheirkhah, Mohammad Taghi; Mokarrami, Mehran; Garcia, Danilo
Abstract: Background: Obtaining reliable data under explicit evaluations is one of the most complicated challenges in assessing drug users' status. Respondents are likely to give answers that are to their advantage or deliberately deceitful. Regarding drug use, intense and inevitable drug craving is known as one of the main causes of relapse and treatment failure. As a matter of fact, drug craving is directly correlated to attentional bias toward drug-related stimuli, while drug-related stimuli capture drug users' attention as a result of craving. Most methods for studying selective attention and attentional bias have been developed for visual modality. However, stimuli that capture drug users' attention are not always visual, they could be auditory. Aims: We examined if a modified word recognition dichotic listening task discriminated between methamphetamine users and non-users. Moreover, we investigated further the reliability and validity of this new paradigm. Methods: A total of 30 adult males participated in the study (15 methamphetamine users and 15 non-users). The word recognition dichotic listening task included two stimuli narratives/sequences (one neutral and one methamphetamine-related) that were presented simultaneously via headphones, one stimuli sequence to each ear. The participants were instructed to only pay attention to the neutral stimuli and to ignore the drug-related stimuli. Afterward, participants were asked to indicate in a list which words they recognized from the listening task and responded to the Desire for Drug Questionnaire, which was modified to address methamphetamine craving. In addition, a month after the experiment, we assessed therapy adherence among participants who were methamphetamine users. Results: Methamphetamine users had a significantly lower performance in the word recognition dichotic task compared to non-users ( t = 4.30, p < .001; Cohen's d = 6.13). Importantly, the average performance on the task was significantly higher among methamphetamine users who continued their treatment one month later compared to those who quitted ( t = −2.56, p < .05; Hedges' g = 1.28). Moreover, the intraclass correlation coefficient with 95% interval confidence for the word recognition dichotic listening task scores was excellent (ICC = 0.90) and the scores were significantly correlated with self-reported methamphetamine craving ( r = −.47, p < .001). Conclusions: The modified word recognition dichotic listening task successfully discriminated between individuals who craved methamphetamine from those who did not. This new paradigm demonstrated high reliability and validity in the present pilot study. Due to the importance of preventing unreliable responses when assessing drug cravings, the current method can be, after further validation, utilized in both research and clinical practices. Abstract : Methamphetamine craving; Implicit assessment; Attentional bias; Dichotic listening paradigm.